Stratification of Surgical Risk in DIEP Breast Reconstruction Based on Classification of Obesity - Patterson, Charles W.; Palines, Patrick A.; Bartow, Matthew J.; Womac, Daniel J.; Zampell, Jamie C.; Dupin, Charles L.; St Hilaire, Hugo; Stalder, Mark W. (Journal of Reconstructive Microsurgery, 2021)
Background From both a medical and surgical perspective, obese breast cancer patients are considered to possess higher risk when undergoing autologous breast reconstruction relative to nonobese patients. However, few studies have evaluated the continuum of risk across the full range of obesity. This study sought to compare surgical risk between the three World Health Organization (WHO) classes of obesity in patients undergoing deep inferior epigastric perforator (DIEP) flap breast reconstruction.Methods A retrospective review of 219 obese patients receiving 306 individual DIEP flaps was performed. Subjects were stratified into WHO obesity classes I (body mass index [BMI]: 30–34), II (BMI: 35–39), and III (BMI: ≥ 40) and assessed for risk factors and postoperative donor and recipient site complications.Results When examined together, the rate of any complication between the three groups only trended toward significance (p = 0.07), and there were no significant differences among rates of specific individual complications. However, logistic regression analysis showed that class III obesity was an independent risk factor for both flap (odds ratio [OR]: 1.71, 95% confidence interval [CI]: 0.91–3.20, p = 0.03) and donor site (OR: 2.34, 95% CI: 1.09–5.05, p = 0.03) complications.Conclusion DIEP breast reconstruction in the obese patient is more complex for both the patient and the surgeon. Although not a contraindication to undergoing surgery, obese patients should be diligently counseled regarding potential complications and undergo preoperative optimization of health parameters. Morbidly obese (class III) patients should be approached with additional caution, and perhaps even delay major reconstruction until specific BMI goals are met.
Keywords: DIEP flap; obesity; breast reconstruction